Legal Ideology as an Element of the Relationship of Civil Society and the State - MELNIKOV, Viktor Yu.; KOLESNIKOV, Yuri A.; KISELEVA, Alla V.; DZHAMALOVA, Bika B. (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
In the article the urgent and important problems arising in connection with necessity of formation state of legal ideology in the form of a constitutional legal ideology, standing on the protection of the rights and freedoms of man and citizen. Special attention is paid to the question of what in legal science there is no uniform approach to the problem of the existence of state ideology in the Russian Federation. Main findings and novelty of the research are, according to the author, that in Russia the existence of a valid binding of the constitutional ideology of the state, functioning within a legal framework that does not violate rights, freedoms and legitimate interests of other persons and aimed at implementing the needs and requirements of the multinational people of the Russian Federation. It can be not only the basis of the national idea, but should serve as a means of uniting social groups and individuals to respond to national goals and objectives. Accordingly, a clearly defined constitutional and legal ideology, with its focus on respect and implement the rights, freedoms and legitimate interests of citizens of Russia, will contribute to stability in the state and society, to be important tool of state-building, guarantee the sustainability of the legal system, the uniform law enforcement practice. Thus, the constitutional and legal ideology – the system of constitutional values, is based on the recognition of the person, its rights and freedoms the Supreme value and the recognition of its right to ideological diversity, the protection of the interests of the state. This follows from the meaning and content of the norms of the Constitution of the Russian Federation, beliefs, ideas, perceptions about the basic foundations of the existence, interaction and development of society and the state in the formation of a legal democratic state.